Breaking bad news of cancer diagnosis - the patient’s perspective - Dhage, Amod S.; Wilkinson, Anne R. (International Journal of Research in Medical Sciences, 2017)
Background: Communication between physicians and patients is a fundamental aspect of cancer care. Bad news could be defined as "any information, which adversely affects an individual’s view of his or her future”. The aim of the research study was to explore the patient’s perspective on receiving cancer news and their expectations regarding the same. Methods: A cross-sectional study was performed in our tertiary care teaching hospital. 50 consenting cancer patients from 18 to 60 years of age were interviewed on the basis of a structured, validated questionnaire. Results: On analysis of the 50 patients ‘answers, it was found that 37 were females and 13 were males, the average age being 50.07 years. The common diagnosis in females was breast cancer (20 patients) and in males it was lung cancer (5 patients). All the patients wanted relatives present with them when the bad news was broken to them. In 66.6% patients, the news was broken by a junior resident, 15% of the doctors didn’t greet the patients, 10% of the patients were told the news suddenly, while 99% of the doctors didn’t explain any positive aspects of the disease related to the treatment outcome. Conclusions: This study provides an insight into the expectations of patients from their physicians with regard to the process of breaking bad news.